KARAKTERISTIK PASIEN HERNIA INGUINALIS DI RSUD Dr. H. CHASAN BOESOIRIE - Permana, Agam; Hidayat, Ferdian; Hasan, Marhaeni (NHM PRESS, 2024)
Inguinal hernia, i.e., protrusion of the abdominal cavity contents through inguinal area, is a common surgical condition. In 2004, its prevalence in Indonesia in reached 18,145 cases, 273 of which succumbed to death. Until now, there has been no research on inguinal hernia patients in North Maluku. The aimed this study to determine the characteristics of age, gender, occupation, nature of the hernia, location of the lump, type of case and orientation of hernia in inguinal hernia patients in North Maluku. This retrospective descriptive study used medical record as data source for age, gender, occupation, nature of the hernia, location of the lump, type of case and orientation of hernia in inguinal hernia patients managed in the dr. H. Chasan Boesoirie General Hospital in 2019-2021. From 103 patients, 32% aged 55-65 years old, 96,1% were male, 43,7% were heavy workers, 36,9% had irreponible hernia, 98,1% had lateral inguinal hernia, 97,1% were new cases, and 63,1% had right-sided hernia. Among inguinal hernia patients managed in the dr. H. Chasan Boesoirie General Hospital in 2019-2021, most were male, aged 55-65 years old, heavy workers, had irreponible hernia, had lateral inguinal hernia, new cases, and had right-sided hernia.